Organization of columnar inputs in the third optic ganglion of a highly visual crab - Bengochea, Mercedes (2014)
Motion information provides essential cues for a wide variety of animal behaviors such as mate, prey, or predator detection. In decapod crustaceans and pterygote insects, visual codification of object motion is associated with visual processing in the third optic neuropile, the lobula. In this neuropile, tangential neurons collect motion information from small field columnar neurons and relay it to the midbrain where behavioral responses would be finally shaped. In highly ordered structures, detailed knowledge of the neuroanatomy can give insight into their function. In spite of the relevance of the lobula in processing motion information, studies on the neuroarchitecture of this neuropile are scant. Here, by applying dextran-conjugated dyes in the second optic neuropile (the medulla) of the crab Neohelice, we mass stained the columnar neurons that convey visual information into the lobula. We found that the arborizations of these afferent columnar neurons lie at four main lobula depths. A detailed examination of serial optical sections of the lobula revealed that these input strata are composed of different number of substrata and that the strata are thicker in the centre of the neuropile. Finally, by staining the different lobula layers composed of tangential processes we combined the present characterization of lobula input strata with the previous characterization of the neuroarchitecture of the crab’s lobula based on reduced-silver preparations. We found that the third lobula input stratum overlaps with the dendrites of lobula giant tangential neurons. This suggests that columnar neurons projecting from the medulla can directly provide visual input to the crab’s lobula giant neurons.